2015
DOI: 10.1017/s000711451400333x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression, stress and feeding styles: towards a framework for theory and research in child obesity

Abstract: Against the background of rising rates of obesity in children and adults in the USA, and modest effect sizes for obesity interventions, the aim of the present narrative review paper is to extend the UNICEF care model to focus on childhood obesity and its associated risks with an emphasis on the emotional climate of the parent-child relationship within the family. Specifically, we extended the UNICEF model by applying the systems approach to childhood obesity and by combining previously unintegrated sets of lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 189 publications
(186 reference statements)
3
97
1
7
Order By: Relevance
“…Accumulating evidence suggests that nutrition could influence the development of numerous psychiatric disorders, including depression [14][15][16][17][18]. A recent meta-analysis including 21 studies demonstrated that high intake of fruit, vegetables, fish and whole grains are associated with a reduced risk of depression [19].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that nutrition could influence the development of numerous psychiatric disorders, including depression [14][15][16][17][18]. A recent meta-analysis including 21 studies demonstrated that high intake of fruit, vegetables, fish and whole grains are associated with a reduced risk of depression [19].…”
Section: Introductionmentioning
confidence: 99%
“…More recent research examining feeding styles – a more global parent feeding measure than practices involving broad parental attitudes regarding feeding – has shown less controlling feeding attitudes to be related to higher child weight status. Specifically using the Caregiver’s Feeding Styles Questionnaire (Hughes et al, 2005) to measure styles, the indulgent feeding (a style in which parents are very responsive to their child during eating episodes but show little structure and boundaries around feeding) has been associated with higher child weight across multiple studies of children ages 3 to 12, see El-Behadli et al [32] for a review. It is posited that lower parental control in feeding may also lessen children’s focus on internal cues of fullness thus reducing self-regulation of eating as well.…”
Section: Environmental Influences On Child Eating Self-regulationmentioning
confidence: 99%
“…It is when the foundations for healthful eating habits that have long-lasting implications for weight status and related comorbidities are established [4,5,7-9]. Several parental characteristics are associated with children’s risk of overweight and obesity including parents’ weight status [1-4], sociodemographic and economic characteristics (eg, income, education) [1-4], and mental health status (eg, depression) [10-19]. Parents, especially mothers, influence their children’s development and maintenance of eating habits and food preferences [2,4-9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Several parental characteristics are associated with children’s risk of overweight and obesity including parents’ weight status [1-4], sociodemographic and economic characteristics (eg, income, education) [1-4], and mental health status (eg, depression) [10-19]. Parents, especially mothers, influence their children’s development and maintenance of eating habits and food preferences [2,4-9,10]. Parental feeding styles and parental feeding practices have been identified as particularly important influences on children’s eating behaviors during early childhood [5,7,8,9-16,20-24].…”
Section: Introductionmentioning
confidence: 99%